STATISTICAL RELATIONSHIP OF ACCOUNTING AND ECONOMICS . - Perry, Kenneth W. (The Accounting Review, 1955)
Abstract The article focuses on the statistical relationship of accounting and economics. Pressures, from both within the accounting profession and without, are constantly being brought to bear on the accountant in an attempt to induce him to change the basis of accounting reports. These ever-increasing pressures often make technical judgment formations by the professional accountant difficult. Many of these forces can be attributed, either directly or indirectly, to ideas of economists. It is the author's belief that accounting and economics are more statistically related and thus more interdependent than is commonly thought. It is also his belief that if the accountant and the economist were both more aware of this relationship, some of these pressures might subside and as a result both professions might derive mutual benefits therefrom. If one considers accounting and economic statistics as merely types of the quantitative method of analysis, the similarities of accounting and statistical methodology must be sought in the characteristics of the quantitative method itself.